AN ANALYSIS OF THE TOTAL PHYSICAL RESPONSE METHOD LEARNING - Sri Hardini (JURNAL PENELITIAN PENDIDIKAN BAHASA DAN SASTRA, 2023)
The title of this Independent Research is An Analysis of The Total Physical Response Method Learning. In this method we will consider a new general approach to foreign language instruction which has been named “ the comprehension approach.” It is called this because of the importance it gives to listening comprehension. All the other methods we have looked at have students speaking in the target language from the first day. Method consistent with the comprehension approach, on the other hand, begin with the listening skill. The idea of focusing on listening comprehension during early foreign language instruction comes from observing how children acquire their mother tongue. The method has been developed from developmental psychology, learning theory and language learning procedures. The Total Physical Response Method Learning is based on the premise that the human brain has a biological program for acquiring any language. The teacher does not correct any student errors during oral communication. In the Total Physical Response Method, students listen and respond to the spoken target language commands of their teacher.